Second Dialect Acquisition: A Sociophonetic Perspective. Issue 11 (November 2015) - Nycz, Jennifer
Abstract: Many people change aspects of their accent after moving to a new region. What kinds of changes are made, and why does it matter? Studies of second dialect acquisition (SDA) indicate that geographically mobile speakers change specific dialect features in ways that reflect the complex interaction of linguistic, social, and developmental factors in language use. This article reviews these findings from a sociophonetic perspective, paying particular attention to their theoretical implications, the methodological issues associated with studying SDA, and avenues for future research.